(untitled) (Bangladesh Journal of Medical Science, 2021)
Airway foreign body aspiration (FBA)is a frequent problem that affects young children, present with acute respiratory distress and cough followed by sudden chocking. Prompt identification and early treatment can save the child from a life-threatening emergency.Delayed diagnosis due to lack of history and clinical suspicion may lead to permanent lung damage, which may be a curse for a lifetime.We share an experience of a 4½-year-old boy who presented with suppurative lung disease was associated with neglected FBA. Early diagnosis and intervention canprevent,and ultimately reduce long-term morbidity and mortality, along with improving the better outcome regarding FBA. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.208-211